Secondary battery and electronic device
By designing the nickel element content gradient distribution in the positive electrode sheet of the secondary battery and using electrolyte with specific additives, the gas production and energy density problems caused by water absorption of the ternary positive electrode materials are solved, and higher energy density and cycling performance are achieved.
Patent Information
- Application Number
- CN202510368356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-07-22
AI Technical Summary
The secondary battery of the ternary positive electrode material is prone to absorb water during the preparation process, resulting in an increase in the water content of the positive electrode sheet and an excessively high residual alkali content, resulting in severe gas production and high circulating expansion during the charging and discharge process.
The positive electrode sheet structure design is adopted. The first material layer has a high nickel element content and the second material layer has a low nickel element content. It is located outside the first material layer. It combines the electrolyte of a specific additive to regulate the content range of nickel elements and additives, reduces water absorption and residual alkali generation, and inhibits the dissolution and side reaction of transition metals.
It effectively reduces the gas production of secondary batteries during charging and discharging, improves energy density and circulation performance, and improves internal gas production problems.
Smart Images

Figure CN120357027A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemistry technology, and particularly to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries are widely used due to advantages such as high specific energy and long cycle life. Among them, the use of ternary cathode materials can effectively improve the energy density of the battery. However, during the preparation of secondary batteries containing ternary cathode materials, the ternary cathode materials are prone to absorbing water when exposed to air, resulting in an increase in the water content of the positive electrode sheet, and thus an excessive residual alkali content in the positive electrode material layer, leading to serious gas generation and a high cycle expansion rate during the charge and discharge process of the secondary battery. Summary of the Invention
[0003] The purpose of this application is to provide a secondary battery and an electronic device to balance the internal gas generation and energy density of the secondary battery.
[0004] It should be noted that in the summary of the invention of this application, lithium-ion batteries are used as examples of secondary batteries to explain this application. However, the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0005] In the first aspect of this application, a secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. The positive electrode sheet includes a positive electrode current collector and a first material layer and a second material layer provided on the surface of the positive electrode current collector. The first material layer is located between the positive electrode current collector and the second material layer; the first material layer includes a first positive electrode material, and the first positive electrode material includes nickel element, cobalt element, and manganese element. Based on the total number of moles of non-lithium metal elements in the first positive electrode material, the molar percentage content of nickel element in the first positive electrode material is N1; the second material layer includes a second positive electrode material, and the second positive electrode material includes nickel element, cobalt element, and manganese element. Based on the total number of moles of non-lithium metal elements in the second positive electrode material, the molar percentage content of nickel element in the second positive electrode material is N2; N1 > N2; the electrolyte includes an additive, and the additive includes at least one of carboxylic ester, fluorinated carboxylic ester, ethyl propionate, propyl propionate, ethyl fluoroacetate, vinylene sulfate, and bicyclic sulfate. Based on the mass of the electrolyte, the mass percentage content W of the additive is 1% to 20%. When the secondary battery satisfies the above characteristics, the water absorption amount is reduced during the preparation process of the positive electrode sheet, the generation of the overall residual alkali in the positive electrode material layer is reduced, and at the same time, the electrolyte containing the above additive is matched, which is beneficial to reducing the gas generation during the charge and discharge process of the secondary battery, improving the internal gas generation of the secondary battery while taking into account the energy density.
[0006] In an embodiment of the present application, 70% ≤ N1 ≤ 95%, 30% ≤ N2 ≤ 50%. By adjusting the values of N1 and N2 within the scope of the present application, the content of nickel element in the first material layer is relatively high, which is beneficial to improving the energy density of the secondary battery. The content of nickel element in the second material layer is relatively low and is located outside the first material layer, which is beneficial to reducing the water absorption amount on the surface of the positive electrode sheet during the preparation process, thereby reducing the generation amount of residual alkali on the surface of the positive electrode sheet. At the same time, by reducing the contact between the high-nickel first material layer and the external environment, the generation amount of residual alkali of the overall positive electrode material layer during the preparation process is reduced, thereby reducing the gas generation during the charge and discharge process of the secondary battery, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0007] In some embodiments of the present application, 80% ≤ N1 ≤ 90%, and / or, 33% ≤ N2 ≤ 40%. By adjusting the values of N1 and N2 within the scope of the present application, the content of nickel element in the first material layer is relatively high, which is beneficial to improving the energy density of the secondary battery. The content of nickel element in the second material layer is relatively low and is located outside the first material layer, which is beneficial to reducing the water absorption amount on the surface of the positive electrode sheet during the preparation process, thereby reducing the generation amount of residual alkali on the surface of the positive electrode sheet. At the same time, by reducing the contact between the high-nickel first material layer and the external environment, the generation amount of residual alkali of the overall positive electrode material layer during the preparation process is reduced, thereby reducing the gas generation during the charge and discharge process of the secondary battery, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0008] In an embodiment of the present application, the additive includes at least one of ethyl fluoroacetate and vinylene sulfate. By adjusting the additive in the electrolyte within the above range, it is beneficial to inhibit the dissolution of transition metals and is not likely to have side reactions with the first material layer and the second material layer, further improving the internal gas generation of the secondary battery.
[0009] In an embodiment of the present application, 3% ≤ W ≤ 10%. By adjusting the mass percentage content W of the additive within the scope of the present application, it is beneficial to inhibit the dissolution of transition metals and is not likely to have side reactions with the first material layer and the second material layer, further improving the internal gas generation during the charge and discharge process of the secondary battery.
[0010] In an embodiment of the present application, the coating mass per unit area of the first material layer is CW1, and the coating mass per unit area of the second material layer is CW2, where 50% ≤ CW1 / (CW1 + CW2)×100% ≤ 90% and 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 50%. By regulating the value of CW1 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the first material layer with a higher nickel element content is relatively high, which is beneficial to providing a relatively large battery capacity under the same mass of the secondary battery and improving the energy density of the secondary battery. At the same time, by regulating the value of CW2 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the second material layer is relatively low and it is located outside the first material layer, with more contact with air, which is beneficial to reducing the generation amount of residual alkali on the surface of the positive electrode plate during the preparation process. At the same time, by reducing the contact between the first material layer with high nickel and the external environment, the generation amount of the overall residual alkali in the positive electrode material layer during the preparation process is reduced, and the gas generation during the charge and discharge process of the secondary battery is reduced. Thus, the first material layer and the second material layer match each other, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0011] In an embodiment of the present application, 70% ≤ CW1 / (CW1 + CW2)×100% ≤ 80%, and / or 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 30%. By regulating the value of CW1 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the first material layer with a higher nickel element content is relatively high, which is beneficial to providing a relatively large battery capacity under the same mass of the secondary battery and improving the energy density of the secondary battery. At the same time, by regulating the value of CW2 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the second material layer is relatively low and it is located outside the first material layer, with more contact with air, which is beneficial to reducing the generation amount of residual alkali on the surface of the positive electrode plate during the preparation process. At the same time, by reducing the contact between the first material layer with high nickel and the external environment, the generation amount of the overall residual alkali in the positive electrode material layer during the preparation process is reduced, and the gas generation during the charge and discharge process of the secondary battery is reduced. Thus, the first material layer and the second material layer match each other, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0012] In an embodiment of the present application, 150 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 350 mg / 1540.24 mm 2 . By regulating the value of CW1 + CW2 within the scope of the present application, the overall positive electrode material layer obtained has a suitable coating mass per unit area, and the first material layer and the second material layer cooperate with each other to further improve the energy density of the secondary battery.
[0013] In an embodiment of the present application, 200 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 300 mg / 1540.24 mm 2 . By adjusting the value of CW1 + CW2 within the scope of the present application, the overall positive electrode material layer has an appropriate coating mass per unit area, and the first material layer and the second material layer cooperate with each other to further improve the energy density of the secondary battery.
[0014] In an embodiment of the present application, the first positive electrode material and the second positive electrode material each independently include a doping element, and the doping element includes at least one of aluminum, magnesium, titanium, tungsten, zirconium, iridium, molybdenum or vanadium; based on the mass of the first positive electrode material, the molar percentage content W1 of the doping element in the first positive electrode material is 0.5% to 5%; based on the mass of the second positive electrode material, the molar percentage content W2 of the doping element in the second positive electrode material is 0.1% to 3%. The doping elements of the first positive electrode material and the second positive electrode material are selected from the above range, and the molar percentage content is adjusted within the scope of the present application, which is beneficial to improving the structural stability of the first positive electrode material and the second positive electrode material, reducing the occurrence probability of side reactions, thereby reducing the occurrence of gas generation during the charge and discharge process of the secondary battery, and further improving the internal gas generation of the secondary battery.
[0015] In some embodiments of the present application, 1% ≤ W1 ≤ 3%, and / or, 0.5% ≤ W2 ≤ 1%. By adjusting the molar percentage content of the doping elements of the first positive electrode material and the second positive electrode material within the scope of the present application, it is beneficial to improving the structural stability of the first positive electrode material and the second positive electrode material, reducing the occurrence probability of side reactions, thereby reducing the occurrence of gas generation during the charge and discharge process of the secondary battery, and further improving the internal gas generation of the secondary battery.
[0016] In an embodiment of the present application, the first material layer includes a first binder and a second binder, and the second material layer includes a third binder; the first binder and the third binder each independently include at least one of polyvinylidene fluoride, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyamideimide, and styrene-butadiene rubber; the second binder includes at least one of polyacrylic acid and a sulfonated polymer, where the sulfonated polymer includes at least one of perfluorosulfonic acid resin, sulfonated polyether ether ketone, sulfonated polystyrene, sulfonated polyimide, and sulfonated polyarylether sulfone. The first binder, the second binder, and the third binder are selected from the above materials. The second binder is acidic and is paired with the first material layer with a high nickel content, which is beneficial to neutralize the residual alkali generated in the first material layer during the preparation process, thereby reducing the overall residual alkali content of the positive electrode material layer, reducing the gas generation during the charge and discharge process of the secondary battery, and at the same time synergistically acting with the first binder and the third binder to improve the adhesion between the overall positive electrode material layer and the positive electrode current collector, improving the internal resistance of the secondary battery, and thus being beneficial to improving the cycle performance of the secondary battery.
[0017] In an embodiment of the present application, based on the mass of the first material layer, the mass percentage content W N1 of the first binder, and the mass percentage content W N2 of the second binder satisfy 0.5% ≤ W N1 + W N2 ≤ 2.5%, 0.3% ≤ W N2 ≤ 1.5%; and / or, based on the mass of the second material layer, the mass percentage content W N3 of the third binder is 0.5% to 2.5%. By regulating the value of W N1 + W N2 and the value of W N2 within the scope of the present application, the acidic second binder is beneficial to neutralize the residual alkali generated by the first positive electrode material during the preparation of the positive electrode sheet, reducing the probability of excessive gas generation during the charge and discharge process of the secondary battery due to a large residual alkali content, further improving the internal gas generation of the secondary battery, and at the same time synergistically acting with the first binder to improve the adhesion between the first material layer, the second binder layer, and the positive electrode current collector; regulating the value of W N3 within the scope of the present application, the third binder synergistically acts with the first binder and the second binder, which is beneficial to improving the adhesion between the overall positive electrode material layer and the positive electrode current collector, further improving the cycle performance of the secondary battery while taking into account the energy density.
[0018] In an embodiment of the present application, the secondary battery satisfies at least one of the following characteristics: (1) Based on the mass of the first material layer, the mass percentage of the first positive electrode material is greater than or equal to 85%; (2) Based on the mass of the second material layer, the mass percentage of the second positive electrode material is greater than or equal to 85%; (3) The first positive electrode material and the second positive electrode material each independently include lithium nickel cobalt manganese oxide. By regulating the mass percentages of the first positive electrode material and the second positive electrode material within the scope of the present application, the first positive electrode material is the main material of the first material layer, and the first positive electrode material has a relatively high nickel content, so that the obtained secondary battery has a high energy density; the second positive electrode material is the main material of the second material layer, and the second material layer is in more contact with air. The second positive electrode material has a suitable nickel content, which is beneficial to reducing the generation amount of residual alkali in the positive electrode material layer during the preparation process and reducing the gas generation during the charge and discharge process of the secondary battery, thereby being beneficial to improving the internal gas generation of the secondary battery while taking into account the energy density.
[0019] The second aspect of the present application provides an electronic device, which includes the secondary battery described in the first aspect of the present application.
[0020] Advantages of the present application:
[0021] The present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte. The positive electrode plate includes a positive electrode current collector and a first material layer and a second material layer provided on the surface of the positive electrode current collector. The first material layer is located between the positive electrode current collector and the second material layer; the first material layer includes a first positive electrode material, and the first positive electrode material includes nickel element, cobalt element and manganese element. Based on the total molar amount of non-lithium metal elements in the first positive electrode material, the molar percentage of nickel element in the first positive electrode material is N1; the second material layer includes a second positive electrode material, and the second positive electrode material includes nickel element, cobalt element and manganese element. Based on the total molar amount of non-lithium metal elements in the second positive electrode material, the molar percentage of nickel element in the second positive electrode material is N2; N1 > N2; the electrolyte includes additives, and the additives include at least one of carboxylic acid ester, fluorinated carboxylic acid ester, ethyl propionate, propyl propionate, ethyl fluoroacetate, vinylene sulfate, bicyclic sulfate. Based on the mass of the electrolyte, the mass percentage W of the additives is 1% to 20%. The secondary battery satisfies the above characteristics, reduces the water absorption amount during the preparation process of the positive electrode plate, reduces the generation of residual alkali in the overall positive electrode material layer, and at the same time matches the electrolyte containing the above additives, which is beneficial to reducing the gas generation during the charge and discharge process of the secondary battery, improving the internal gas generation of the secondary battery while taking into account the energy density.
[0022] Of course, it is not necessary for any product or method implementing the present application to simultaneously achieve all the above-mentioned advantages. Description of the Drawings
[0023] To more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other embodiments can also be obtained based on these drawings.
[0024] Figure 1 It is a schematic structural diagram of the positive electrode plate along its thickness direction in an implementation scheme of the present application. Specific embodiments
[0025] The following will clearly and completely describe the technical solutions in the present application in conjunction with the embodiments and drawings of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application fall within the protection scope of the present application.
[0026] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is taken as an example of a secondary battery to explain the present application. However, the secondary battery of the present application is not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0027] The first aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, and an electrolyte, as Figure 1As shown, the positive electrode plate 10 includes a positive electrode current collector 110 and a first material layer 120 and a second material layer 130 provided on the surface of the positive electrode current collector 110. The first material layer 120 is located between the positive electrode current collector 110 and the second material layer 130. The first material layer includes a first positive electrode material, and the first positive electrode material includes nickel element, cobalt element and manganese element. Based on the total molar amount of non-lithium metal elements in the first positive electrode material, the molar percentage content of nickel element in the first positive electrode material is N1; the second material layer includes a second positive electrode material, and the second positive electrode material includes nickel element, cobalt element and manganese element. Based on the total molar amount of non-lithium metal elements in the second positive electrode material, the molar percentage content of nickel element in the second positive electrode material is N2; N1 > N2. A higher nickel element content in the ternary positive electrode material can provide a higher energy density. However, when the nickel element content is too high, the positive electrode material is prone to absorb water during the preparation process of the positive electrode plate, resulting in an increase in the water content of the positive electrode plate. Especially when the water content on the surface of the positive electrode plate is too high, the overall residual alkali content of the positive electrode material layer is too high, which aggravates the internal gas generation during the charge and discharge process of the secondary battery. Therefore, by controlling the molar percentage content of nickel element in the first positive electrode material and the second positive electrode material to satisfy the above relationship, the nickel element content in the first material layer is relatively high, which can provide a higher energy density. The nickel element content in the second material layer is relatively low and is located outside the first material layer, having more contact with air, which can reduce the water absorption amount on the surface of the positive electrode plate during the preparation process, thereby reducing the generation amount of residual alkali on the surface of the positive electrode plate. At the same time, by reducing the contact between the high-nickel first material layer and the external environment, the water absorption amount in the first material layer is reduced, the generation of residual alkali in the positive electrode plate during the preparation process is reduced, and the gas generation during the charge and discharge process of the secondary battery is reduced, so as to improve the internal gas generation of the secondary battery while taking into account the energy density.
[0028] In an embodiment of the present application, the electrolyte includes an additive, and the additive includes at least one of carboxylic acid ester, fluorinated carboxylic acid ester, ethyl propionate, propyl propionate, ethyl fluoroacetate, vinylene sulfate, and bicyclic sulfate. Based on the mass of the electrolyte, the mass percentage content W of the additive is 1% to 20%. In an embodiment of the present application, 3% ≤ W ≤ 10%. For example, the mass percentage content W of the additive can be 1%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range composed of any two of these values. When the mass percentage content of the additive is too small, such as less than 1%, the improvement of internal gas generation in the secondary battery is not obvious; when the mass percentage content of the additive is too large, such as greater than 20%, it is easy to form a relatively thick solid electrolyte interface (SEI) film on the surface of the negative electrode sheet, which affects the cycle performance of the secondary battery. Therefore, by introducing the above additive into the electrolyte and controlling its mass percentage content W within the scope of the present application, the dissolution of transition metals can be inhibited, and side reactions with the first material layer and the second material layer are not likely to occur, improving the internal gas generation during the charge and discharge process of the secondary battery.
[0029] Thus, the secondary battery satisfies the above characteristics, reduces the water absorption during the preparation process of the positive electrode sheet, reduces the generation of residual alkali in the overall positive electrode material layer, and at the same time matches the electrolyte containing the above additive, which is beneficial to reducing the gas generation during the charge and discharge process of the secondary battery, thereby improving the internal gas generation of the secondary battery while taking into account the energy density.
[0030] In one embodiment of the present application, 70% ≤ N1 ≤ 95%. In some embodiments of the present application, 80% ≤ N1 ≤ 90%. For example, N1 can be 70%, 72%, 74%, 76%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 92%, 94%, 95% or a range composed of any two of these values. In one embodiment of the present application, 30% ≤ N2 ≤ 50%. In one embodiment of the present application, 33% ≤ N2 ≤ 40%. For example, N2 can be 30%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 42%, 44%, 46%, 48%, 50% or a range composed of any two of these values. By adjusting the values of N1 and N2 within the scope of the present application, the content of nickel element in the first material layer is relatively high, which is beneficial to improving the energy density of the secondary battery. The content of nickel element in the second material layer is relatively low and is located outside the first material layer, which is beneficial to reducing the water absorption on the surface of the positive electrode plate during the preparation process, thereby reducing the generation amount of residual alkali on the surface of the positive electrode plate. At the same time, by reducing the contact between the high-nickel first material layer and the external environment, the generation amount of overall residual alkali in the positive electrode material layer during the preparation process is reduced, thereby reducing the gas generation during the charge and discharge process of the secondary battery, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0031] In one embodiment of the present application, the additive includes at least one of ethyl fluoroacetate and vinylene sulfate. By adjusting the additive in the electrolyte within the above range, it is beneficial to inhibit the dissolution of transition metals and is not likely to have side reactions with the first material layer and the second material layer, further improving the internal gas generation of the secondary battery.
[0032] In an embodiment of the present application, the coating mass per unit area of the first material layer is CW1, and the coating mass per unit area of the second material layer is CW2, 50% ≤ CW1 / (CW1 + CW2)×100% ≤ 90%. In an embodiment of the present application, 70% ≤ CW1 / (CW1 + CW2)×100% ≤ 80%. For example, the value of CW1 / (CW1 + CW2) can be 50%, 55%, 60%, 65%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 85%, 90% or a range composed of any two of these ratios. In an embodiment of the present application, 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 50%. In an embodiment of the present application, 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 30%. For example, the value of CW2 / (CW1 + CW2) can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 35%, 40%, 45%, 50% or a range composed of any two of these ratios. By adjusting the value of CW1 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the first material layer with a higher nickel element content is relatively high, which is beneficial to providing more battery capacity under the same mass of the secondary battery and is beneficial to improving the energy density of the secondary battery; at the same time, by adjusting the value of CW2 / (CW1 + CW2) within the scope of the present application, the percentage of the coating mass per unit area of the second material layer is relatively low and is located outside the first material layer, with more contact with air, which is beneficial to reducing the generation amount of residual alkali on the surface of the positive electrode plate during the preparation process. At the same time, by reducing the contact between the high-nickel first material layer and the external environment, the generation amount of the overall residual alkali in the positive electrode material layer during the preparation process is reduced, and the gas generation during the charge and discharge process of the secondary battery is reduced. Thus, the first material layer and the second material layer match each other, further improving the internal gas generation of the secondary battery while taking into account the energy density.
[0033] In an embodiment of the present application, 150 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 350 mg / 1540.24 mm 2 。In an embodiment of the present application, 200 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 300 mg / 1540.24 mm 2 。For example, CW1 + CW2 can be 150 mg / 1540.24 mm 2 、180 mg / 1540.24 mm 2 、200 mg / 1540.24 mm 2 、220 mg / 1540.24 mm 2, 250 mg / 1540.24 mm 2 , 280 mg / 1540.24 mm 2 , 300 mg / 1540.24 mm 2 , 320 mg / 1540.24 mm 2 , 350 mg / 1540.24 mm 2 Or a range composed of any two of these values. By adjusting the value of CW1 + CW2 within the scope of this application, the overall positive electrode material layer has an appropriate coating mass per unit area, and the first material layer and the second material layer cooperate with each other to further improve the energy density of the secondary battery.
[0034] In an embodiment of this application, the first positive electrode material and the second positive electrode material each independently include a doping element, and the doping element includes at least one of aluminum, magnesium, titanium, tungsten, zirconium, iridium, molybdenum, or vanadium; based on the mass of the first positive electrode material, the molar percentage content W1 of the doping element in the first positive electrode material is 0.5% to 5%. In an embodiment of this application, 1% ≤ W1 ≤ 3%. For example, W1 can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5% or a range composed of any two of these values. In an embodiment of this application, based on the mass of the second positive electrode material, the molar percentage content W2 of the doping element in the second positive electrode material is 0.1% to 3%. In an embodiment of this application, 0.5% ≤ W2 ≤ 1%. For example, W2 can be 0.1%, 0.2%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3% or a range composed of any two of these values. The doping elements of the first positive electrode material and the second positive electrode material are selected from the above range, and adjusting the molar percentage content within the scope of this application is beneficial to improving the structural stability of the first positive electrode material and the second positive electrode material, reducing the probability of side reactions, thereby reducing the gas generation during the charge and discharge process of the secondary battery, and further improving the internal gas generation of the secondary battery.
[0035] In an embodiment of the present application, the first material layer includes a first binder and a second binder, and the second material layer includes a third binder; the first binder and the third binder each independently include at least one of polyvinylidene fluoride, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyamideimide, styrene-butadiene rubber; the second binder includes at least one of polyacrylic acid and a sulfonated polymer, wherein the sulfonated polymer includes at least one of perfluorosulfonic acid resin, sulfonated polyether ether ketone, sulfonated polystyrene, sulfonated polyimide, and sulfonated polyarylether sulfone. The first binder, the second binder, and the third binder are selected from the above materials. The second binder is acidic and is paired with the first material layer with a high nickel content, which is beneficial to neutralize the residual alkali generated in the first material layer during the preparation process, thereby reducing the overall residual alkali content of the positive electrode material layer, being beneficial to reducing gas generation during the charge and discharge process of the secondary battery, and at the same time synergistically acting with the first binder and the third binder to improve the adhesion between the overall positive electrode material layer and the positive electrode current collector, improving the internal resistance of the secondary battery, and thus being beneficial to improving the cycle performance of the secondary battery.
[0036] In an embodiment of the present application, based on the mass of the first material layer, the mass percentage content W of the first binder N1 , and the mass percentage content W of the second binder N2 , 0.5% ≤ W N1 + W N2 ≤ 2.5%, 0.3% ≤ W N2 ≤ 1.5%. For example, the value of W N1 + W N2 can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5% or a range composed of any two of these numerical values; the mass percentage content W of the second binder N2 can be 0.3%, 0.5%, 0.7%, 0.9%, 1%, 1.2%, 1.5% or a range composed of any two of these numerical values. By regulating the value of W N1 + W N2 and the value of W N2 within the scope of the present application, the acidic second binder is beneficial to neutralize the residual alkali generated by the first positive electrode material during the preparation of the positive electrode sheet, reducing the probability of excessive gas generation during the charge and discharge process of the secondary battery due to a large residual alkali content, further improving the internal gas generation of the secondary battery, and at the same time synergistically acting with the first binder, being beneficial to improving the adhesion between the first material layer, the second binder layer, and the positive electrode current collector, further improving the cycle performance of the secondary battery while taking into account the energy density.
[0037] In an embodiment of the present application, based on the mass of the second material layer, the mass percentage content W of the third binderN3 is from 0.5% to 2.5%. For example, the value of W N3 can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, or a range composed of any two of these values. By adjusting the value of W N3 within the scope of this application, the third binder, the first binder, and the second binder work together, which is beneficial to improving the adhesion between the overall positive electrode material layer and the positive electrode current collector, further improving the cycle performance of the secondary battery while taking into account the energy density.
[0038] In one embodiment of this application, based on the mass of the first material layer, the mass percentage content of the first positive electrode material is greater than or equal to 85%. In one embodiment of this application, based on the mass of the first material layer, the mass percentage content of the first positive electrode material is greater than or equal to 85% and less than or equal to 97.4%. For example, the mass percentage content of the first positive electrode material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 97.4%, or a range composed of any two of these values. By adjusting the mass percentage content of the first positive electrode material within the scope of this application, since the first positive electrode material is the main material of the first material layer and the first positive electrode material has a relatively high nickel content, the obtained secondary battery has a relatively high energy density.
[0039] In one embodiment of this application, based on the mass of the second material layer, the mass percentage content of the second positive electrode material is greater than or equal to 85%. In one embodiment of this application, based on the mass of the second material layer, the mass percentage content of the second positive electrode material is greater than or equal to 85% and less than or equal to 97.4%. For example, the mass percentage content of the second positive electrode material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 97.4%, or a range composed of any two of these values. By adjusting the mass percentage content of the second positive electrode material within the scope of this application, since the second positive electrode material is the main material of the second material layer and the second material layer is in more contact with air, and the second positive electrode material has a suitable nickel content, it is beneficial to reduce the generation amount of residual alkali in the positive electrode material layer during the preparation process, reduce the gas generation during the charge and discharge process of the secondary battery, and thus is beneficial to improving the internal gas generation of the secondary battery while taking into account the energy density.
[0040] In one embodiment of this application, the first positive electrode material and the second positive electrode material each independently include lithium nickel cobalt manganese oxide. When the first positive electrode material includes lithium nickel cobalt manganese oxide and the lithium nickel cobalt manganese oxide does not contain the above doping elements, the chemical formula of the lithium nickel cobalt manganese oxide is Li n11 Ni x11 Co y11 Mnz11 When it is O2, 0.95 ≤ n11 ≤ 1.05, x11 + y11 + z11 = 1, 0.7 ≤ x11 ≤ 0.95, 0.01 ≤ y11 ≤ 0.3, 0.01 ≤ z11 ≤ 0.2;
[0041] When the second positive electrode material includes lithium nickel cobalt manganese oxide and the lithium nickel cobalt manganese oxide does not contain the above doping elements, the chemical formula of the lithium nickel cobalt manganese oxide is Li n12 Ni x12 Co y12 Mn z12 When it is O2, 0.95 ≤ n12 ≤ 1.05, x12 + y12 + z12 = 1, 0.3 ≤ x12 ≤ 0.5, 0.01 ≤ y12 ≤ 0.5, 0.2 ≤ z12 ≤ 0.4;
[0042] When the first positive electrode material includes lithium nickel cobalt manganese oxide and the lithium nickel cobalt manganese oxide contains the above doping elements, the chemical formula of the lithium nickel cobalt manganese oxide is Li n21 Ni x21 Co y21 Mn z21 M21 m21 When it is O2, M21 is selected from at least one of aluminum, magnesium, titanium, tungsten, zirconium, iridium, molybdenum or vanadium, 0.95 ≤ n21 ≤ 1.05, x21 + y21 + z21 + m21 = 1, 0.7 ≤ x21 ≤ 0.95, 0.01 ≤ y21 ≤ 0.295, 0.01 ≤ z21 ≤ 0.2, 0.005 ≤ m21 ≤ 0.05;
[0043] When the second positive electrode material includes lithium nickel cobalt manganese oxide and the lithium nickel cobalt manganese oxide contains the above doping elements, the chemical formula of the lithium nickel cobalt manganese oxide is Li n22 Ni x22 Co y22 Mn z22 M22 m22 When it is O2, M22 is selected from at least one of aluminum, magnesium, titanium, tungsten, zirconium, iridium, molybdenum or vanadium, 0.95 ≤ n22 ≤ 1.05, x22 + y22 + z22 + m22 = 1, 0.3 ≤ x22 ≤ 0.5, 0.01 ≤ y22 ≤ 0.499, 0.2 ≤ z22 ≤ 0.4, 0.001 ≤ m22 ≤ 0.03.
[0044] In some embodiments of the present application, when the lithium nickel cobalt manganese oxide does not contain the above doping elements, the first positive electrode material may include, but is not limited to, LiNi 0.7 Co 0.15 Mn 0.15 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.8 Co 0.1 Mn0.1 O2 (NCM811), LiNi 0.85 Co 0.08 Mn 0.07 O2, LiNi 0.88 Co 0.06 Mn 0.06 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.95 Co 0.03 Mn 0.02 At least one of O2, the second cathode material may include but is not limited to LiNi 0.3 Co 0.3 Mn 0.4 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2 (NCM111), LiNi 0.4 Co 0.4 Mn 0.2 O2, LiNi 0.5 Co 0.3 Mn 0.2 At least one of O2 (NCM532).
[0045] In some embodiments of the present application, when lithium nickel cobalt manganese oxide contains the above doping elements, the first cathode material may include but is not limited to LiNi 0.79 Co 0.1 Mn 0.1 Mg 0.01 O2, LiNi 0.795 Co 0.1 Mn 0.1 Mg 0.005 O2, LiNi 0.79 Co 0.1 Mn 0.1 Mg 0.01 O2, LiNi 0.77 Co 0.1 Mn 0.1 Mg 0.03 O2, LiNi 0.75 Co 0.1 Mn 0.1 Mg 0.05 O2, LiNi 0.79 Co 0.1 Mn 0.1 Al 0.01 At least one of O2, the second cathode material may include but is not limited to LiNi 0.339 Co 0.33 Mn 0.33 Al0.001 O2, LiNi 0.335 Co 0.33 Mn 0.33 Al 0.005 O2, LiNi 0.339 Co 0.33 Mn 0.33 Al 0.01 O2, LiNi 0.31 Co 0.33 Mn 0.33 Al 0.03 O2, LiNi 0.33 Co 0.33 Mn 0.33 Mg 0.01 at least one of O2.
[0046] In some embodiments of the present application, the first material layer may further include a first conductive agent, and the mass percentage content of the first conductive agent in the first material layer is 0.1% to 12.5%; the second material layer may further include a second conductive agent, and the mass percentage content of the second conductive agent in the second material layer is 0.1% to 12.5%. For example, the mass percentage content of the first conductive agent may be 0.1%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 12.5% or a range composed of any two of these values; the mass percentage content of the second conductive agent may be 0.1%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 12.5% or a range composed of any two of these values.
[0047] In some embodiments of the present application, there are no particular restrictions on the types of the first conductive agent and the second conductive agent, as long as the object of the present application can be achieved. For example, the first conductive agent and the second conductive agent may each independently include, but are not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials, or conductive polymers. The conductive carbon black may include, but is not limited to, at least one of acetylene black or Ketjen black. The above carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or nanofibers. The above metal materials may include, but are not limited to, metal powders and / or metal fibers. Specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The above conductive polymers may include, but are not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole.
[0048] The present application does not particularly limit the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet can be as follows: (1) Mix the first positive electrode material, the first conductive agent, the first binder, and the second binder, add a solvent, and formulate into a slurry, and stir evenly to obtain the first material layer slurry; (2) Mix the second positive electrode material, the second conductive agent, and the third binder, add a solvent, and formulate into a slurry, and stir evenly to obtain the second material layer slurry; (3) Uniformly coat the first material layer slurry on one surface of the positive electrode current collector, dry it, and then uniformly coat the second material layer slurry on one surface of the first material layer away from the positive electrode current collector, and dry it to obtain a positive electrode sheet with the first material layer and the second material layer coated on one side; (4) Repeat the above coating process on the other surface of the positive electrode current collector, and dry it to obtain a positive electrode sheet with the first material layer and the second material layer coated on both sides.
[0049] In the present application, the first positive electrode material and the second positive electrode material with different nickel contents can be obtained by purchase, and their nickel contents can be tested by inductively coupled plasma mass spectrometry, and the first positive electrode material and the second positive electrode material with the required nickel content can be selected.
[0050] In the present application, the first positive electrode material and the second positive electrode material with different doping element types and contents can be obtained by purchase, and the types and contents of their doping elements can be tested by inductively coupled plasma mass spectrometry, and the first positive electrode material and the second positive electrode material with the required doping element types and contents can be selected.
[0051] In the present application, the positive electrode sheet includes a positive electrode current collector and a first material layer and a second material layer provided on the surface of the positive electrode current collector. The above "first material layer and second material layer provided on the surface of the positive electrode current collector" means that the first material layer and the second material layer can be provided on one surface of the positive electrode current collector along its thickness direction, or can be provided on two surfaces of the positive electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode current collector, or can be a partial area of the surface of the positive electrode current collector. The present application does not particularly limit it, as long as the purpose of the present application can be achieved.
[0052] The present application does not particularly limit the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include aluminum foil, aluminum alloy foil, or a composite current collector (such as an aluminum-carbon composite current collector), etc.
[0053] The present application does not particularly limit the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 8 μm to 20 μm.
[0054] In the present application, the total thickness of the first material layer and the second material layer can be 30 μm to 150 μm.
[0055] In the present application, the secondary battery further includes a separator. There is no particular limitation on the separator in the present application, as long as the object of the present application can be achieved. For example, the material of the separator may include, but is not limited to, at least one of polyolefins (PO) mainly composed of polyethylene (PE) and polypropylene (PP), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of the separator may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a rolled film, or a spun film.
[0056] In some embodiments of the present application, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric, or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0057] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer, an inorganic layer, or a layer formed by mixing a polymer and an inorganic substance.
[0058] In some embodiments of the present application, the inorganic layer includes inorganic particles and an inorganic layer binder. There is no particular limitation on the inorganic particles in the present application. For example, the inorganic particles may include at least one of alumina, silica, magnesia, titania, hafnium dioxide, tin dioxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. There is no particular limitation on the inorganic layer binder in the present application. For example, the inorganic layer binder may be at least one of the negative electrode binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).
[0059] In the present application, there is no particular limitation on the thickness of the separator, as long as the object of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0060] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "the negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or a partial area of the surface of the negative electrode current collector. There is no special limitation in the present application as long as the purpose of the present application can be achieved.
[0061] There is no special limitation on the negative electrode current collector in the present application as long as the purpose of the present application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. Exemplarily, the composite current collector can be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0062] The negative electrode material layer includes a negative electrode active material. There is no special limitation on the negative electrode active material in the present application as long as the purpose of the present application can be achieved. For example, the negative electrode active material can include, but is not limited to, natural graphite, artificial graphite, mesophase microcarbon spheres, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, lithiated TiO2-Li4Ti5O with a spinel structure 12 or at least one of Li-Al alloys.
[0063] In some embodiments of the present application, the negative electrode material layer may further include a negative electrode conductive agent and a negative electrode binder. The present application does not particularly limit the types of the negative electrode conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include, but is not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials, or conductive polymers. The conductive carbon black may include, but is not limited to, at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include, but is not limited to, vapor-grown carbon fibers (VGCF) and / or nanofibers. The above-mentioned metal materials may include, but are not limited to, metal powders and / or metal fibers. Specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The above-mentioned conductive polymers may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. For example, the negative electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamideimide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.
[0064] The present application does not particularly limit the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 120 μm.
[0065] The present application does not particularly limit the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0066] Optionally, the negative electrode sheet may further include a negative electrode conductive layer, and the negative electrode conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application does not particularly limit the composition of the negative electrode conductive layer, and it may be a commonly used conductive layer in the art. For example, the negative electrode conductive layer includes a negative electrode conductive layer conductive agent and a negative electrode conductive layer binder. The present application does not particularly limit the negative electrode conductive layer conductive agent and the negative electrode conductive layer binder. For example, it may be at least one of the above-mentioned negative electrode conductive agent and the above-mentioned negative electrode binder.
[0067] In the present application, the electrolyte includes a lithium salt and a non-aqueous solvent.
[0068] The present application places no particular limitation on the lithium salt, as long as the object of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methylsulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium tris(trifluoromethylsulfonyl)methyl (LiC(SO2CF3)3), lithium hexafluorosilicate (LiSiF6), lithium bis(oxalato)borate (LiBOB), and lithium difluoroborate (LiF2OB). The present application places no particular limitation on the content of the lithium salt in the electrolyte, as long as the object of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage content of the lithium salt is 8% to 15%. For example, the mass percentage content of the lithium salt may be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range composed of any two of these values.
[0069] The present application places no particular limitation on the non-aqueous solvent, as long as the object of the present application can be achieved. For example, the non-aqueous solvent may include, but is not limited to, at least one of carbonate compounds, carboxylate compounds, ether compounds, or other organic solvents.
[0070] The above-mentioned carbonate compounds may include, but are not limited to, at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The above-mentioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinylene ethylene carbonate (VEC). The fluorinated carbonate compounds may include, but are not limited to, at least one of fluorinated ethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethyl ethylene carbonate. The above-mentioned carboxylic ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone or caprolactone. The above-mentioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0071] This application does not particularly limit the content of the non-aqueous solvent in the electrolyte as long as the object of this application can be achieved. For example, based on the mass of the electrolyte, the mass percentage content of the non-aqueous solvent is 70% to 85%. For example, the mass percentage content of the non-aqueous solvent may be 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 85% or a range composed of any two of these values.
[0072] The secondary battery further includes a housing for accommodating the positive electrode plate, the separator, the negative electrode plate, and the electrolyte, as well as other components known in the field of secondary batteries. This application does not limit the above-mentioned other components. This application has no special restrictions on the housing, and it can be a housing well-known in the art as long as it can achieve the purpose of this application. For example, the housing can be a hard shell housing or a flexible housing. The material of the hard shell housing can be metal, and this application does not limit the type of metal. Any known metal hard shell housing in the art can be used as long as it can achieve the purpose of this application. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0073] The preparation process of the secondary battery of this application is well-known to those skilled in the art, and this application has no special restrictions. For example, the preparation process of the secondary battery can include but is not limited to the following steps: stacking the positive electrode plate, the separator, and the negative electrode plate in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly, placing the electrode assembly into the housing, injecting the electrolyte into the housing and sealing it to obtain the secondary battery. Or, stack the positive electrode plate, the separator, and the negative electrode plate in sequence, and then fix the four corners of the entire laminated structure with tape to obtain a laminated electrode assembly, place the electrode assembly into the housing, inject the electrolyte into the housing and seal it to obtain the secondary battery. In addition, an overcurrent protection element, a guide plate, etc. can also be placed in the housing as needed to prevent the pressure inside the secondary battery from rising and overcharging / discharging.
[0074] In some embodiments of this application, the secondary battery of this application can include but is not limited to: lithium metal secondary batteries, lithium ion secondary batteries (lithium ion batteries), lithium polymer secondary batteries, or lithium ion polymer secondary batteries, etc. In some embodiments of this application, the secondary battery includes a lithium ion battery.
[0075] The second aspect of this application provides an electronic device, which includes the secondary battery described in the first aspect of this application.
[0076] This application has no special limitations on the type of the electronic device, and it can be any electronic device known in the prior art. In some embodiments of this application, the electronic device can include but is not limited to: laptop computers, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, liquid crystal televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, motorized bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors, etc.
[0077] Examples
[0078] Hereinafter, examples and comparative examples are given to illustrate the embodiments of the present application more specifically. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0079] Testing method and device:
[0080] Sampling:
[0081] At an ambient temperature of 25°C, the lithium-ion battery is disassembled, the positive electrode sheet is taken out, washed with dimethyl carbonate, and then placed in an oven and dried at 80°C for 12 h to obtain a positive electrode sheet sample.
[0082] Unless otherwise specified below, the above samples are used for testing.
[0083] Testing of the type and mass percentage content of additives in the electrolyte:
[0084] First, the lithium-ion battery is discharged at a constant current of 0.5C to 3V at 25°C, then the packaging bag is removed, the tab is cut off, the remaining electrode assembly is wound up and put into a centrifuge tube, and the electrolyte sample is collected by standing. The electrolyte sample is centrifuged in a centrifuge, and the upper clear liquid is taken as the test sample.
[0085] The type and content of additives in the electrolyte test sample are tested by gas chromatography-mass spectrometry (GC-MS). Among them, the type of additive is determined by comparing with the standard card.
[0086] Testing of the molar percentage content of nickel element and doping element in the first positive electrode material and the second positive electrode material:
[0087] The cross-section of the positive electrode sheet along the thickness direction is ion-polished. Under the observation of a scanning electron microscope combined with an energy spectrometer, the layer with a higher nickel content is identified as the first material layer, and the layer with a lower nickel content is identified as the second material layer. And according to the observation of the scanning electron microscope combined with the energy spectrometer, the type of doping element is confirmed.
[0088] The first material layer is located between the positive electrode current collector and the second material layer. The thickness of the first material layer is measured and recorded as h1, and the thickness of the second material layer is recorded as h2. According to the measured thickness, the positive electrode material layer with a thickness less than h2 is scraped off, and the obtained powder is used as the second material layer powder. Then, the positive electrode material layer with a thickness greater than h2 is scraped off, and the positive electrode material layer is continuously scraped to obtain the powder as the first material layer powder.
[0089] The first material layer powder is calcined in a nitrogen atmosphere at 600 °C for 2 h to obtain the first cathode material sample. Then, 0.4 g of the sample is dissolved in 10 mL of aqua regia (concentrated hydrochloric acid (HCl) and concentrated nitric acid (HNO3) in a volume ratio of 3:1), dissolved at 180 °C for 30 min, and then cooled to room temperature. The sample is made up to 100 mL.
[0090] Standard curve: Prepare a series of nickel standard solutions, cobalt standard solutions, manganese standard solutions, and doped element standard solutions with different concentrations. Use an inductively coupled plasma mass spectrometry (ICP-MS) instrument to measure the mass numbers of the standard solutions, and plot the standard curves of nickel, cobalt, manganese, and doped elements. When the types and number of doped elements can be confirmed by EDS, the number of standard curves of doped elements corresponds to the number of types of doped elements.
[0091] Sample testing: Introduce the prepared sample solution into the ICP-MS instrument to measure the contents of nickel, cobalt, manganese, and doped elements. According to the standard curves, obtain the mass concentrations of nickel, cobalt, manganese, and doped elements respectively, convert to obtain the masses of nickel, cobalt, manganese, and doped elements, and then obtain the number of moles n1 of nickel, the number of moles n2 of cobalt, the number of moles n3 of manganese, and the number of moles n4 of doped elements. Take the sum of the number of moles n1 of nickel, the number of moles n2 of cobalt, the number of moles n3 of manganese, and the number of moles n4 of doped elements as the total number of moles of non-lithium metal elements;
[0092] The molar percentage content N1(%) of nickel in the first cathode material = n1 / (n1 + n2 + n3 + n4) × 100%; The molar percentage content W1(%) of doped elements in the first cathode material = n4 / (n1 + n2 + n3 + n4) × 100%.
[0093] Replace the first material layer powder with the second material layer powder, and refer to the above steps to obtain the molar percentage content N2 of nickel in the second cathode material and the molar percentage content W2 of doped elements in the second cathode material.
[0094] 80 °C 6 h storage thickness expansion rate test method:
[0095] Charge the lithium-ion battery at a constant current of 0.5C to 4.4V, then charge it at a constant voltage to 0.05C. Place the lithium-ion battery at 80 °C for 6 h. Use a flat thickness gauge with a 1000 g weight to measure the thicknesses of the lithium-ion battery before and after high-temperature storage as H0 and H1 respectively, and calculate the 80 °C 6 h storage thickness expansion rate (%) = (H1 - H0) / H0 × 100%.
[0096] Volume energy density test:
[0097] At 25 °C, the lithium-ion battery is charged at a constant current of 0.5C to 4.4V, then charged at a constant voltage to 0.05C, and left standing for 5 minutes; then discharged at a constant current of 0.2C to 3.0V and left standing for 5 minutes. The discharge energy at this time is recorded as the energy (Wh) of the lithium-ion battery; and the length, width, and height of the lithium-ion battery are measured, and the volume (L) of the lithium-ion battery is calculated. The energy density (Wh / L) of the lithium-ion battery is calculated by the following formula = energy of the lithium-ion battery (Wh) / volume of the lithium-ion battery (L).
[0098] 45 °C 600-cycle capacity retention rate test:
[0099] At 45 °C, the lithium-ion battery is charged at a constant current of 0.5C to 4.4V, then charged at a constant voltage to 0.05C, and then discharged at 0.5C to 3.0V to complete one cycle, which is recorded as the first cycle. The discharge capacity of the first cycle is recorded and left standing for 5 minutes. Then, repeat the above steps for 600 cycles and record the discharge capacity after cycling.
[0100] Capacity retention rate (%) = (discharge capacity after 600 cycles / discharge capacity of the first cycle) × 100%.
[0101] Example 1-1
[0102] <Preparation of the positive electrode sheet>
[0103] (1) Mix the first positive electrode material NCM811, the first conductive agent acetylene black, and the first binder polyvinylidene fluoride (PVDF) in a mass ratio of 97:2:1, add N-methylpyrrolidone (NMP) as a solvent, and prepare a slurry with a solid content of 75 wt%. After vacuum stirring evenly, the first material layer slurry is obtained;
[0104] (2) Mix the second positive electrode material NCM111, the second conductive agent acetylene black, and the third binder PVDF in a mass ratio of 97:2:1, add NMP as a solvent, and prepare a slurry with a solid content of 75 wt%. After vacuum stirring evenly, the second material layer slurry is obtained;
[0105] (3) Uniformly coat the first material layer slurry on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, dry it at 120 °C, and then uniformly coat the second material layer slurry on one surface of the first material layer away from the positive electrode current collector to obtain a positive electrode sheet with a single-sided coating of the first material layer and the second material layer. Among them, the coating mass per unit area CW1 of the first material layer is 200 mg / 1540.24 mm 2 , and the coating mass per unit area CW2 of the second material layer is 50 mg / 1540.24 mm 2, the value of CW1 + CW2 is 250 mg / 1540.24 mm 2 . Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode plate with the first material layer and the second material layer coated on both sides. After drying at 120 °C and cold pressing, and then through cutting and welding the tab, a positive electrode plate with a specification of 74 mm × 867 mm is obtained for use. Among them, the overall compaction density of the first material layer and the second material layer is 4.23 g / cm 3 .
[0106] <Preparation of negative electrode plate>
[0107] Mix artificial graphite as the negative electrode active material, styrene-butadiene rubber as the negative electrode binder, and acetylene black as the negative electrode conductive agent according to a mass ratio of 97.4:1.4:1.2, add deionized water as a solvent, and formulate a slurry with a solid content of 45 wt%. After stirring evenly with a vacuum mixer, a negative electrode slurry is obtained. Coat the negative electrode slurry evenly on one surface of a negative electrode current collector copper foil with a thickness of 6 μm, and dry it at 120 °C to obtain a negative electrode plate with a negative electrode material layer coated on one side. The coating weight of the negative electrode material layer is 142 mg / 1540.24 mm 2 . Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode plate with the negative electrode material layer coated on both sides. After drying at 120 °C and cold pressing, and then through cutting and welding the tab, a negative electrode plate with a specification of 78 mm × 875 mm is obtained for use. Among them, the thickness of the single-sided negative electrode material layer is 54.5 μm, and the compaction density of the negative electrode material layer is 1.735 g / cm 3 .
[0108] <Preparation of electrolyte>
[0109] In an environment with a water content of less than 10 ppm, mix dimethyl carbonate, diethyl carbonate, and ethylene carbonate according to a mass ratio of 1:1:1 to obtain a non-aqueous solvent. Then add electrolyte salt LiPF6 and ethyl fluoroacetate to the non-aqueous solvent and mix evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass percentage content of the electrolyte salt is 12.5%, the mass percentage content of ethyl fluoroacetate is 5%, and the rest is the non-aqueous solvent.
[0110] <Separator>
[0111] Use a porous polyethylene film with a thickness of 7 μm (provided by Celgard) as the separator.
[0112] <Preparation of lithium-ion battery>
[0113] Stack the above-prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator in the middle between the positive electrode sheet and the negative electrode sheet to play an isolation role, and wind them to obtain an electrode assembly. Place the electrode assembly into an aluminum-plastic film housing, remove moisture at 80 °C, inject the above-prepared electrolyte, and obtain a lithium-ion battery through processes of vacuum packaging, standing, formation, degassing, and trimming. Among them, the upper limit voltage of formation is 4.2 V, the formation temperature is 70 °C, and the formation standing time is 2 h.
[0114] Examples 1-2 to 1-6
[0115] Except for adjusting the mass percentage content of the additive in the electrolyte according to Table 1, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0116] Examples 1-7 to 1-23
[0117] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1.
[0118] Examples 2-1 to 2-4, Examples 2-10 to 2-13
[0119] Except for adjusting the relevant parameters according to Table 2, the rest is the same as Example 1-1. When the mass percentage content of the third binder changes, the mass percentage content of the second positive electrode material changes accordingly, and the mass percentage content of the second conductive agent remains unchanged.
[0120] Example 2-5
[0121] Except for preparing the slurry of the first material layer in the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.
[0122] <Preparation of the slurry of the first material layer>
[0123] Mix the first positive electrode material NCM811, the first conductive agent acetylene black, the first binder PVDF, and the second binder polyacrylic acid in a mass ratio of 96.5:2:0.5:1, add NMP as a solvent, and formulate it into a slurry with a solid content of 75 wt%, and obtain the slurry of the first material layer after vacuum stirring evenly.
[0124] Examples 2-6 to 2-9
[0125] Except for adjusting the relevant parameters according to Table 2, the rest is the same as Example 2-5. When the mass percentage content of the first binder and the second binder changes, the mass percentage content of the first positive electrode material changes accordingly, and the mass percentage content of the first conductive agent remains unchanged.
[0126] Examples 3-1 to 3-9
[0127] Except for adjusting the relevant parameters according to Table 3, the rest is the same as that of Example 1-1.
[0128] Comparative Example 1
[0129] Except that the electrolyte does not contain additives, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt remains unchanged, the rest is the same as that of Example 1-1.
[0130] Comparative Examples 2 to 3
[0131] Except that the mass percentage content of the additive in the electrolyte is adjusted as shown in Table 1, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt remains unchanged, the rest is the same as that of Example 1-1.
[0132] Comparative Examples 4 to 6
[0133] Except for adjusting the relevant parameters according to Table 1, the rest is the same as that of Example 1-1.
[0134] The preparation parameters and performance parameters of each example and comparative example are shown in Tables 1 to 3.
[0135] Table 1
[0136]
[0137]
[0138] Note: " / " in Table 1 indicates the absence of corresponding preparation parameters, substances or performance parameters.
[0139] Table 2
[0140]
[0141]
[0142] Note: " / " in Table 2 indicates the absence of corresponding preparation parameters, substances or performance parameters.
[0143] As can be seen from Examples 1-1 to 1-23 and Comparative Examples 1 to 6, when the molar percentage content N1 of nickel element in the first cathode material is greater than the molar percentage content N2 of nickel element in the second cathode material, and the type and mass percentage content W of the additive in the electrolyte are within the scope of the present application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45°C, indicating that the lithium-ion battery obtained in the present application can balance internal gas generation and energy density. Among them, in Comparative Example 1 and Comparative Example 2, since the mass percentage content of the additive in the electrolyte is lower than the scope of the present application, the obtained lithium-ion battery has a higher thickness expansion rate during storage at 80°C for 6 hours and a lower capacity retention rate after 600 cycles at 45°C; in Comparative Example 3, since the content of the additive in the electrolyte is too high, although the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours, its capacity retention rate after 600 cycles at 45°C and energy density are both low; in Comparative Example 4, since N2 is higher than the scope of the present application and N1 = N2, although the obtained lithium-ion battery has a higher energy density, it has a higher thickness expansion rate during storage at 80°C for 6 hours and a lower capacity retention rate after 600 cycles at 45°C; in Comparative Example 5, since N1 is lower than the scope of the present application and N1 = N2, although the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours and a higher capacity retention rate after 600 cycles at 45°C, its energy density is low; in Comparative Example 6, since N1 and N2 are not within the scope of the present application and N1 < N2, the obtained lithium-ion battery has a higher thickness expansion rate during storage at 80°C for 6 hours, a lower capacity retention rate after 600 cycles at 45°C, and a lower energy density. It can be seen that it is difficult for the lithium-ion batteries in Comparative Examples 1 to 6 to balance internal gas generation and energy density.
[0144] As can be seen from Examples 1-1 to 1-6, when the mass percentage content W of the additive in the electrolyte is within the scope of the present application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45°C, indicating that the lithium-ion battery obtained in the present application can balance internal gas generation and energy density. Further, when 3% ≤ W ≤ 10%, it can further balance internal gas generation and energy density.
[0145] The molar percentage content N1 of nickel element in the first positive electrode material and the molar percentage content N2 of nickel element in the second positive electrode material will affect the internal gas generation and energy density of the secondary battery. It can be seen from Example 1-1, Example 1-9 to Example 1-13, and Example 1-14 to Example 1-18 that when the molar percentage content N1 of nickel element in the first positive electrode material and the molar percentage content N2 of nickel element in the second positive electrode material are within the scope of this application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80 °C for 6 h, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45 °C. This shows that the lithium-ion battery obtained in this application can improve the energy density while taking into account the internal gas generation.
[0146] It can be seen from Example 1-1, Example 1-19 to Example 1-23 that when the values of CW1 / (CW1 + CW2) and CW2 / (CW1 + CW2) are within the scope of this application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80 °C for 6 h, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45 °C. This shows that the lithium-ion battery obtained in this application can take into account both internal gas generation and energy density.
[0147] It can be seen from Example 1-1, Example 2-1 to Example 2-4 that when the value of CW1 + CW2 is within the scope of this application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80 °C for 6 h, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45 °C. This shows that the lithium-ion battery obtained in this application can take into account both internal gas generation and energy density.
[0148] It can be seen from Example 1-1, Example 2-5 to Example 2-9 that when the first material layer contains the second binder, the thickness expansion rate of the obtained lithium-ion battery during storage at 80 °C for 6 h is improved, and it has a higher volume energy density and a higher capacity retention rate after 600 cycles at 45 °C. This shows that the lithium-ion battery obtained in this application can take into account both internal gas generation and energy density.
[0149] It can be seen from Example 2-5 to Example 2-9 that when the type and mass percentage content of the second binder are within the scope of this application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80 °C for 6 h, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45 °C. This shows that the lithium-ion battery obtained in this application can improve the internal gas generation while taking into account the energy density.
[0150] As can be seen from Examples 1-1, 2-11 to 2-13, when the type and mass percentage content of the third binder are within the scope of the present application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45°C. This shows that the lithium-ion battery obtained in the present application can improve internal gas generation while taking into account the energy density.
[0151] Table 3
[0152]
[0153]
[0154] Note: " / " in Table 3 indicates that the corresponding preparation parameters, substances, or performance parameters do not exist.
[0155] As can be seen from Examples 1-1, 3-1 to 3-9, when the first cathode material and the second cathode material contain doping elements, the obtained lithium-ion battery has an improved thickness expansion rate during storage at 80°C for 6 hours, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45°C. This shows that the lithium-ion battery obtained in the present application can improve internal gas generation while taking into account the energy density.
[0156] As can be seen from Examples 3-1 to 3-9, when the type and mass percentage content of the doping elements in the first cathode material and the second cathode material are within the scope of the present application, the obtained lithium-ion battery has a lower thickness expansion rate during storage at 80°C for 6 hours, a higher volume energy density, and a higher capacity retention rate after 600 cycles at 45°C. This shows that the lithium-ion battery obtained in the present application can improve internal gas generation while taking into account the energy density.
[0157] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprising", "including" or any other variation thereof are intended to cover non-exclusive inclusion, so that a process, method, or article including a series of elements not only includes those elements, but also includes other elements not expressly listed, or elements inherent to such process, method, or article.
[0158] Each embodiment in this specification is described in a related manner. For the same or similar parts between the embodiments, reference can be made to each other. The key points of each embodiment are the differences from other embodiments.
[0159] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included within the scope of protection of the present application.
Claims
1. A secondary battery, which includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. The positive electrode sheet includes a positive current collector and a first material layer and a second material layer provided on the surface of the positive current collector. The first material layer is located between the positive current collector and the second material layer; The first material layer includes a first positive electrode material. The first positive electrode material includes nickel element, cobalt element, and manganese element. Based on the total molar amount of non-lithium metal elements in the first positive electrode material, the molar percentage content of the nickel element in the first positive electrode material is N1; The second material layer includes a second positive electrode material. The second positive electrode material includes nickel element, cobalt element, and manganese element. Based on the total molar amount of non-lithium metal elements in the second positive electrode material, the molar percentage content of the nickel element in the second positive electrode material is N2; N1 > N2; The electrolyte includes an additive. The additive includes at least one of carboxylic acid ester, fluorinated carboxylic acid ester, ethyl propionate, propyl propionate, ethyl fluoroacetate, vinylene sulfate, and bicyclic sulfate. Based on the mass of the electrolyte, the mass percentage content W of the additive is 1% to 20%.
2. The secondary battery according to claim 1, wherein, 70% ≤ N1 ≤ 95%, 30% ≤ N2 ≤ 50%.
3. The secondary battery according to claim 2, wherein, 80% ≤ N1 ≤ 90%, and / or, 33% ≤ N2 ≤ 40%.
4. The secondary battery according to claim 1, wherein, The additive includes at least one of ethyl fluoroacetate and vinylene sulfate.
5. The secondary battery according to claim 1, wherein, 3%≤W≤10%。 6. The secondary battery according to any one of claims 1 to 5, wherein, The coating mass per unit area of the first material layer is CW1, and the coating mass per unit area of the second material layer is CW2. 50% ≤ CW1 / (CW1 + CW2)×100% ≤ 90%, 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 50%.
7. The secondary battery according to claim 6, wherein 70% ≤ CW1 / (CW1 + CW2)×100% ≤ 80%, and / or, 10% ≤ CW2 / (CW1 + CW2)×100% ≤ 30%.
8. The secondary battery according to claim 6, wherein 150 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 350 mg / 1540.24 mm 2 。 9. The secondary battery according to claim 8, wherein, 200 mg / 1540.24 mm 2 ≤ CW1 + CW2 ≤ 300 mg / 1540.24 mm 2 。 10. The secondary battery according to any one of claims 1 to 5, wherein, The first positive electrode material and the second positive electrode material each independently include a doping element. The doping element includes at least one of aluminum, magnesium, titanium, tungsten, zirconium, iridium, molybdenum, or vanadium; Based on the mass of the first positive electrode material, the molar percentage content W1 of the doping element in the first positive electrode material is 0.5% to 5%; Based on the mass of the second positive electrode material, the molar percentage content W2 of the doping element in the second positive electrode material is 0.1% to 3%.
11. The secondary battery according to claim 10, wherein, 1% ≤ W1 ≤ 3%, and / or, 0.5% ≤ W2 ≤ 1%.
12. The secondary battery according to any one of claims 1 to 5, wherein, The first material layer includes a first binder and a second binder, and the second material layer includes a third binder; The first binder and the third binder each independently include at least one of polyvinylidene fluoride, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyamideimide, and styrene-butadiene rubber; The second binder includes at least one of polyacrylic acid and a sulfonated polymer, where the sulfonated polymer includes at least one of perfluorosulfonic acid resin, sulfonated polyether ether ketone, sulfonated polystyrene, sulfonated polyimide, and sulfonated polyarylether sulfone.
13. The secondary battery according to claim 12, wherein, Based on the mass of the first material layer, the mass percentage content W of the first binder N1 , the mass percentage content W of the second binder N2 , 0.5% ≤ W N1 +W N2 ≤ 2.5%, 0.3% ≤ W N2 ≤ 1.5%; and / or, Based on the mass of the second material layer, the mass percentage content W of the third binder N3 is 0.5% to 2.5%.
14. The secondary battery according to any one of claims 1 to 13, which satisfies at least one of the following characteristics: (1) Based on the mass of the first material layer, the mass percentage content of the first positive electrode material is greater than or equal to 85%; (2) Based on the mass of the second material layer, the mass percentage content of the second positive electrode material is greater than or equal to 85%; (3) The first positive electrode material and the second positive electrode material each independently include lithium nickel cobalt manganate.
15. An electronic device, which includes the secondary battery according to any one of claims 1 to 14.